Energy rehabilitation studies of a large group of historical buildings: a case study - Teixeira, A. Rego (2013)
In this paper, energy rehabilitation studies of a large group of historical buildings are assessed. A general methodology and some particular constraints are discussed. For a case study including 65 buildings in one of Lisbon’s historical centres, the methodology used, the proposed energy-efficient measures and the results in terms of heating energy savings and summer thermal convert are presented and discussed.